15th AIAA Aviation Technology, Integration, and Operations Conference 2015
DOI: 10.2514/6.2015-3327
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Detect and Avoid (DAA) Displays for Unmanned Aircraft Systems: The Effect of Information Level and Display Location on Pilot Performance

Abstract: A consortium of government, industry and academia is currently working to establish minimum operational performance standards for Detect and Avoid (DAA) and Control and Communications (C2) systems in order to enable broader integration of Unmanned Aircraft Systems (UAS) into the National Airspace System (NAS). One subset of these performance standards will need to address the DAA display requirements that support an acceptable level of pilot performance. From a pilot's perspective, the DAA task is the maintena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 12 publications
0
39
0
Order By: Relevance
“…1,2 In the United States, simulation tests as well as flight tests have provided supporting information for defining a DAA Well Clear 1, 3 (DWC) and requirements for the alerting and guidance performance. [4][5][6][7] Prototype DAA algorithms have also been developed to alerting and guidance research. [8][9][10] These developments enabled the RTCA Special Committee 228 (SC-228) to publish the Minimum Operational Performance Standards (MOPS) for DAA systems 11 and air-to-air radar 12 in 2017.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In the United States, simulation tests as well as flight tests have provided supporting information for defining a DAA Well Clear 1, 3 (DWC) and requirements for the alerting and guidance performance. [4][5][6][7] Prototype DAA algorithms have also been developed to alerting and guidance research. [8][9][10] These developments enabled the RTCA Special Committee 228 (SC-228) to publish the Minimum Operational Performance Standards (MOPS) for DAA systems 11 and air-to-air radar 12 in 2017.…”
Section: Introductionmentioning
confidence: 99%
“…The results reported above provide a definitive answer as to the source of the improved pilot performance for the advanced conditions in Fern et al (2015). As shown here, the display conditions that included auto-resolutions (D3 and D4) consistently resulted in the fastest pilot response times, while the displays that lacked the tool (D1 and D2) often led to the slowest pilot responses.…”
Section: Discussionmentioning
confidence: 53%
“…Specifically, Fern et al (2015) reported significantly faster Initial Edit Times, Total Edit Times and Total Response Times when the advanced tools were present. Due to the presence of multiple conflict detection and resolution tools, however, Fern et al (2015) could not report on the cause of the differences in pilot performance.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Specific attention has been paid to identifying the traffic display features that minimize pilot response times and the frequency and severity of losses of DAA well clear (LoDWC) [6][7][8][9][10]. The results of these studies informed the development of the Phase 1 DAA MOPS traffic display requirements, which specified a minimum set of information that DAA traffic displays must provide to UAS pilots.…”
Section: Daa Alerting and Guidancementioning
confidence: 99%